The Effect of Vascular Endothelial Growth Factor on Bone Marrow Mesenchymal Stem Cell Engraftment in Rat Fibrotic Liver upon Transplantation - Ke Yuan; Chunyou Lai; Lingling Wei; Tianhang Feng; Qinyan Yang; Tianying Zhang; Tao Lan; Yutong Yao; Guangming Xiang; Xiaolun Huang (Stem Cells International)
Background. According to existing related experiments and research reports, stem cell transplantation therapy has been shown to have a positive effect on the recovery of liver fibrosis/cirrhosis, but for some reason, this therapy still cannot be widely used in clinical work. One of the reasons that cannot be ignored is the low quantity of exogenous stem cells transplanted into the liver in vivo. Thus, we investigated whether the use of the vascular endothelial growth factor (VEGF) can increase the number of stem cell transplants and improve the efficacy of stem cell transplantation therapy. Methods. Using a Sprague-Dawley rat liver fibrosis model, we transplanted into fibrosis liver allograft bone marrow mesenchymal stem cells (BMSCs) which were labelled with chlormethylbenzamido-1,1-dioctadecyl-3,3,3′3′-tetramethylin-docarbocyamine (CM-DiI) or injected VEGF adenovirus solution through the tail vein or conducted the above two operations simultaneously. The cell surface receptor profile of BMSC was examined by flow cytometry and immunofluorescence staining. Hepatic sinusoidal vascular leakage was measured with Evan’s blue dye assay. Paraffin section staining, immunofluorescent staining, RT-qPCR (quantitative reverse transcription polymerase chain reaction), and Western blot were used to evaluate hepatic pathological changes and physiology function. Result. The in vivo study indicated that, comparing with other groups of rats, the rats with combined treatment of BMSC transplantation and VEGF injection exhibited obvious reduction in liver fibrosis. Evan’s blue dye assay suggests that after injecting with VEGF adenovirus solution, the rat’s hepatic sinusoidal permeability would be increased. We confirmed the expression of very late antigen-4 (VLA4, integrin α4β1) on rat BMSCs and the elevated expression of vascular adhesion molecule-1 (VCAM-1) in the hepatic sinusoidal endothelial cells. In addition, the analysis of CM-DiI-labeled BMSCs showed that the BMSC+VEGF group exhibited better cell engraftment and that the engrafted cells were mainly distributed in the hepatic parenchyma. Furthermore, compared with the other situation, it is best to reconstitute the liver secretion and regeneration function of rats after combined application of VEGF and BMSC. Conclusion. We showed that VEGF promotes the engraftment of BMSCs in liver fibrosis, enhances liver regeneration, and improves liver function. These outcomes may be related to the increasing hepatic sinusoidal endothelium permeability and VCAM-1-increased expression.